cis-Acting components of human papillomavirus (HPV) DNA replication: linker substitution analysis of the HPV type 11 origin. - Russell, J (1995)
Papillomavirus DNA replication requires the viral trans-acting factors E1 and E2 in addition to the host cell's general replication machinery. The origins of DNA replication in bovine and human papillomavirus genomes have been localized to a specific part of the upstream regulatory region (URR) which includes recognition sites for E1 and E2 proteins. To fine map cis-acting elements influencing human papillomavirus type 11 (HPV-11) DNA replication and to determine the relative contributions of such sites, we engineered consecutive linker substitution mutations across a region of 158 bp in the HPV-11 origin and tested mutant origins for replication function in a cell-based transient replication assay. Our results both confirm and extend the findings of others. E2 binding sites are the major cis components of HPV-11 DNA replication, and there is evidence for synergy between these sites. Differential capacity of the three E2 binding sites within the origin to affect replication may be attributed, at least in part, to context. At least one E2 binding site is essential for replication. The imperfect AT-rich palindrome of the E1 helicase binding site is not essential since replication occurs even in the absence of this sequence. However, replication is enhanced by the presence of the palindromic sequence in the HPV-11 origin. Sequence components adjacent to the E1 and E2 binding sites, comprising AT-rich and purine-rich elements and the consensus TATA box sequence, probably contribute to the overall efficiency of replication, though they are nonessential. None of the other cis elements of the HPV-11 origin region analyzed seems to influence replication significantly in the system described. The HPV-11 origin of DNA replication therefore differs from those of the other papovaviruses, simian virus 40 and polyomavirus, inasmuch as an intact helicase binding site and adjacent AT-rich components, while influential, are not absolutely essential.